2011
DOI: 10.1093/bja/aer288
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of clopidogrel therapy: the effects on in-hospital cardiac morbidity in older patients with hip fractures

Abstract: The length of withdrawal of clopidogrel therapy perioperatively was associated with a significantly increased incidence of ACS. An association between shorter withdrawal and increased blood transfusion requirements was also seen. The study emphasizes the cardiovascular risks of routinely interrupting clopidogrel therapy in this at-risk population and that a more considered, individualized, evidenced-based approach is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
0
34
0
1
Order By: Relevance
“…At our hospital we are trying to improve early access to FIB in order to avoid the complications described above, and are developing a training program to enable emergency staff to perform FIBs at their initial assessment. This has been shown to be achievable and provides safe and effective analgesia in the emergency department [3].We agree with the accompanying editorial calling for a more prominent role for nerve blocks in the pain management of this patient population [4]. We also suggest that the delayed use of FIBs on the analgesic ladder is incorrect, and will potentially create a serious complication that will tarnish the reputation of a very useful block.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…At our hospital we are trying to improve early access to FIB in order to avoid the complications described above, and are developing a training program to enable emergency staff to perform FIBs at their initial assessment. This has been shown to be achievable and provides safe and effective analgesia in the emergency department [3].We agree with the accompanying editorial calling for a more prominent role for nerve blocks in the pain management of this patient population [4]. We also suggest that the delayed use of FIBs on the analgesic ladder is incorrect, and will potentially create a serious complication that will tarnish the reputation of a very useful block.…”
mentioning
confidence: 67%
“…Clopidogrel should not be stopped and there is some evidence that blood loss is not increased when fractured femur patients undergo surgery [2]. There is also evidence that stopping the drug and waiting may actually harm the patient [3]. Options for regional anaesthesia will be limited but general anaesthesia is a reasonable option.…”
Section: A Replymentioning
confidence: 99%
See 1 more Smart Citation
“…22 Furthermore, Collyer et al stated that no haematomas were reported for 25 hip fracture patients on clopidogrel who had spinal anaesthesia. 23 The plasma half-life of clopidogrel is approximately six hours. 24 Its concentration falls to <2% after 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing number of patients on clopidogrel therapy are presenting for urgent hip fracture surgery. Early withdrawal of clopidogrel has been shown to be associated with increased incidence of acute coronary events [13] .…”
Section: Discussionmentioning
confidence: 99%